Citicoline Combination Therapy for Major Depressive Disorder: A Randomized, Double-Blind, Placebo-Controlled Trial. Issue 1 (January 2017) - Roohi-Azizi, Mahtab; Arabzadeh, Somaye; Amidfar, Meysam; Salimi, Samrand; Zarindast, Mohammad Reza; Talaei, Ali; Akhondzadeh, Shahin
Abstract : Objective: Residual symptoms of major depressive disorder are a source of long-term morbidity. New therapeutic strategies are required to alleviate this morbidity and enhance patient quality of life. Citicoline has been used for vascular accidents and has been effective in cognitive rehabilitation. It has been used successfully to reduce craving in patients with substance abuse disorder and for mood management of bipolar disorder. Here, we test citicoline effectiveness as an adjuvant therapy in major depression. Method: A double-blind randomized trial was designed on 50 patients with major depressive disorder who were under treatment with citalopram. Patients were allocated to 2 groups and received citicoline (100 mg twice a day) or placebo as an adjuvant treatment for 6 weeks. Depressive symptoms were assessed by the Hamilton Depression Rating Scale (HDRS) at baseline and at weeks 2, 4, and 6. Results: Significantly greater improvement was observed in the HDRS scores of the citicoline group compared with the placebo group from baseline to weeks 2, 4, and 6 ( P s = 0.030, 0.032, and 0.021, respectively). Repeated-measures general linear model demonstrated a significant effect for time × treatment interaction on the HDRS score ( F 2.10, 101.22 = 3.12, P = 0.04). Remission rate was significantly higher in the citicoline group compared with the placebo group ( P = 0.045). Conclusions: Citicoline was an effective adjuvant to citalopram in the therapy of major depressive disorder.